TINJAUAN THEOY RESOURCES BASED VIEW (RBV) DALAM PENINGKATAN KOMPETENSI KOLABORASI ANTAR ORGANISASI - Azis Fathoni; Heru Sri Wulan; Dewi Fatmasari (ITB AAS Indonesia Surakarta, 2026)
The purpose of this paper is to analyze the framework of the Resource Based View (RBV) theory in the perspective of ontology, epistemology and axiology that is put forward in the discussion of strategic management and especially relating to the strengths and weaknesses of the organization. Based on a historical approach and literature review from the opinions of experts who discuss RBV theory in relation to capabilities and competencies in synergizing several partnership models of an organization in creating superior competitiveness. The antecedent of this research is the rationality of the emergence of collaborative organizations that cooperate must have strategic resources and the ability/competence to manage resources. The consequences of this research are partnerships with a systems approach considering the influence of the organizational environment on organizational growth. This paper puts forward the concept of partnership formulation based on RBV values ​​moderated by innovative collaboration principles.